Inhibitory Effect of Lithospermic Acid on the HIV-1 Nucleocapsid Protein - Mori, Mattia (Molecules, 2020)
The HIV-1 nucleocapsid protein (NC) is a desirable target in antiretroviral therapy due to its high conservation among HIV-1 strains, and to its multiple and crucial roles in the HIV-1 replication cycle. Natural products represent a valuable source of NC inhibitors, with the catechol group being a privileged scaffold in NC inhibition. By coupling molecular modeling with NMR spectroscopy and fluorescence-based assays, we disclosed lithospermic acid, a catechol derivative extracted from Salvia miltiorrhizza, as a potent and chemically stable non-covalent inhibitor of the NC. Being different from other catechol derivative reported so far, lithospermic acid does not undergo spontaneous oxidation in physiological conditions, thus becoming a profitable starting point for the development of efficient NC inhibitors.